ADMINISTRATED OF SNAKE WOOD (Strychnos lucida) TO DECREASED ABNORMALITY SPERMATOZOA OF MICE (Mus musculus) DIABETES MELLITUS MODELING - Kunu, Marissa Beatrix; Baszary, Chomsa Dintasari Umi; Killay, Amos (RUMPHIUS, 2020)
Diabetes mellitus, known as diabetes or blood sugar disease, is a group of chronic diseases characterized by increased blood sugar level (hyperglycemia). Prolonged hyperglycemia conditions will cause an increase in ROS (Reactive Oxygen Spesies) production by the mitochondria, which then cause damage to the mitochondrial membrane resulting in loss of function of the mitochondrial membrane potential and can induce sperm cells apoptosis. This study aims to determine effect of kayu ular (Strychnos lucida) steeping on decreasing spermatozoa abnormalities of mice (Mus musculus) diabetes mellitus model. The result showed that administration of kayu ular steeping at concentration of 2,6gr/50ml was signicantly reduced (P<0.05) spermatozoa abnormality. This dose is the most effective concentration to decreased the spermatozoa abnormality of mice. This though to be due to the active compounds found in steeping kayu ular (Strychnos lucida) which can counteract free radicals due to diabetes mellitus that decreasing spermatozoa abnormalities.